Impacts of red imported fire ants Solenopsis invicta on survivorship of hatchlings of the broad-snouted caiman Caiman latirostris - Parachu Marco, Maria Virginia (2013)
Background: Oviparous vertebrate species are often vulnerable to predation by red imported fire ants (RIFAs, Solenopsis invicta) in natural environments. The necrotic action of the venom can cause localized infections, with subsequent effects on survival and growth. Despite the significant impacts of RIFAs in regions where they have been introduced, very little is known about the competitive mechanisms of RIFAs with other species in their native habitat. We tested whether the survival and growth of hatchlings of the broad-snouted caiman Caiman latirostris were affected by different exposure times to RIFAs. Results: We observed that an increased exposure time to RIFAs caused a decrease in C. latirostris survival. However, the subsequent growth of C. latirostris hatchlings was not affected by the time of exposure to the ants. Conclusions: S. invicta can cause negative effects for other species in places where it is native. The mechanisms of S. invicta toxicity to caimans are not known; these data could help model the effects of S. invicta on C. latirostris survival, in turn fostering a better understanding of wild population dynamics.